If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + 30y = 660 Solving 15x + 30y = 660 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30y' to each side of the equation. 15x + 30y + -30y = 660 + -30y Combine like terms: 30y + -30y = 0 15x + 0 = 660 + -30y 15x = 660 + -30y Divide each side by '15'. x = 44 + -2y Simplifying x = 44 + -2y
| (12+n)x(13+n)=200 | | x-27=5x+1 | | -2(3d+1)-2d=-26 | | -5x-5+5(x-5)=-(-5-x)-4 | | 16h^2-8h=0 | | y+7.8=14 | | 11x-(5+4x)= | | 4x+3x+14x=2x+7x+5x | | 6x+40=2x+8 | | -2.2(5c+1)=19.8 | | 1-x-(5+4x)= | | 130x=60 | | (5x+4)2=28 | | 8z-3(5z^2-3)-(4z^2+z-5)= | | (5x+5)=(5x) | | -3(2y-7)=10y+85 | | 9(2a+7)=81 | | (5x+5)=(7x-19) | | Y=-2x^5-5x | | 15=3(v-7) | | 7x+14y+28= | | 2x+12+x+9-3x=117 | | 4y=-2x-5 | | 4(2d+3)-3d=42 | | 3b(2b-5)=6(b^2-5b+6)+139 | | F(x)=-4x+12x-8 | | 9-9x-6-6x=6 | | 2x+50=10x+10 | | 4x+4=6x-11 | | y=x+5-x+7 | | 15m-(-8m-5)= | | t*5-6=9 |